2019
DOI: 10.1038/s41398-019-0647-7
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic control of ADAMTS2 expression through cAMP/CREB and ERK: molecular effects of antipsychotics

Abstract: A better understanding of the molecular mechanisms that participate in the development and clinical manifestations of schizophrenia can lead to improve our ability to diagnose and treat this disease. Previous data strongly associated the levels of deregulated ADAMTS2 expression in peripheral blood mononuclear cells (PBMCs) from patients at first episode of psychosis (up) as well as in clinical responders to treatment with antipsychotic drugs (down). In this current work, we performed an independent validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…For example, expression of ADAMTS2, which was upregulated across all brain regions examined in our study, was increased in peripheral blood samples from subjects with SZ, and decreased following antipsychotic treatment (Ruso‐Julve et al., 2019; Sainz et al., 2019). Furthermore, antipsychotics were shown to inhibit dopamine‐induced expression of ADAMTS2 in neuronal cell culture, suggesting that antipsychotics partially correct for increased ADAMTS2 expression that we observed in subjects with SZ (Ruso‐Julve et al., 2019).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, expression of ADAMTS2, which was upregulated across all brain regions examined in our study, was increased in peripheral blood samples from subjects with SZ, and decreased following antipsychotic treatment (Ruso‐Julve et al., 2019; Sainz et al., 2019). Furthermore, antipsychotics were shown to inhibit dopamine‐induced expression of ADAMTS2 in neuronal cell culture, suggesting that antipsychotics partially correct for increased ADAMTS2 expression that we observed in subjects with SZ (Ruso‐Julve et al., 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Antipsychotics, lithium and VPA have all been reported to impact ECM molecules in rodent and human studies. In many cases, the effects of these drugs are opposite to changes observed in subjects with SZ, suggesting that these treatments may achieve therapeutic efficacy in part by correcting for changes in ECM molecules (Ruso‐Julve et al., 2019; Sainz et al., 2019; Yukawa et al., 2018). For example, expression of ADAMTS2, which was upregulated across all brain regions examined in our study, was increased in peripheral blood samples from subjects with SZ, and decreased following antipsychotic treatment (Ruso‐Julve et al., 2019; Sainz et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These few reports supporting that CBD attenuates aberrant status of ERK1/2 phosphorylation which is related to schizophrenia-related symptomatology, converge with studies regarding antipsychotic drugs effect on p-ERK1/2. In particular it is shown that antipsychotics per se induce opposite effects of p-ERK state as compared to p-ERK alterations in psychosis or schizophrenia models ( Ruso-Julve et al, 2019 ). These reports concerning antipsychotic action on p-ERK are in line with present findings concerning CBD effects.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, miR-132 was highly expressed in the forebrain and was regulated by cAMP response element-binding (CREB) and extracellular signal regulated kinase (ERK) signaling. Both CREB and ERK are targets of antipsychotic drugs ( 91 , 116 ). On the contrary, Miller et al.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%